2019
DOI: 10.1016/j.iccn.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Staff perception of obstacles and facilitators when providing end of life care in critical care units of two teaching hospitals: A survey design

Abstract: Objective: To determine perceptions of Jordanian critical care staff about obstacles and facilitators to end-of-life care. Research Methodology: The "National Survey of Critical Care Nurses' Perceptions of Endof-Life Care" was adapted and distributed to 143 critical care nurses (n=110) and physicians (n=33) in two Jordanian hospitals. Nurses and physicians completed items about perceived obstacles to end-of-life care. Nurses only completed items about facilitators to end-of-life care. Results: The overall resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 22 publications
3
24
1
Order By: Relevance
“…Providing end-of-life care is challenging in a Jordanian intensive care context, which is attributed to the fraught of cultural issues including over-optimistic hope, in addition to other religious and medico-legal concerns (Almansour, 2015;Almansour, Ahmad, et al, 2020;Almansour et al, 2019). Khader (2017) of family and physicians to refer patients to palliative care because it might be considered a failure of their cure and (4) religious misconceptions leading the patient to suffer intolerable pain as a form of salvation that also often prevent them from seeking medical attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing end-of-life care is challenging in a Jordanian intensive care context, which is attributed to the fraught of cultural issues including over-optimistic hope, in addition to other religious and medico-legal concerns (Almansour, 2015;Almansour, Ahmad, et al, 2020;Almansour et al, 2019). Khader (2017) of family and physicians to refer patients to palliative care because it might be considered a failure of their cure and (4) religious misconceptions leading the patient to suffer intolerable pain as a form of salvation that also often prevent them from seeking medical attention.…”
Section: Introductionmentioning
confidence: 99%
“…Providing end‐of‐life care is challenging in a Jordanian intensive care context, which is attributed to the fraught of cultural issues including over‐optimistic hope, in addition to other religious and medico‐legal concerns (Almansour, 2015; Almansour, Ahmad, et al, 2020; Almansour et al, 2019). Khader (2017) summarises the main cultural challenges hindering the provision of palliative care services in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Therefore presenting with increased complexity, prognostication can also be difficult and providing care is challenging. 4,5 This change in the nature of ICU population accompany the global aging population and the emergence of chronic, progressive illnesses (eg, cancer, cardiovascular diseases, and respiratory diseases), as well as continuing developments in lifeprolonging technologies. 6,7 Although the proportion of people dying in hospitals has been decreasing for years, 3,8 the hospital is still the most common place for death to occur in the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, so profound have these effects been that fundamental changes in the thoughts (Aslakson et al 2010 ; Monteiro et al 2016 ; Simmonds 1996 ; Svantesson et al 2003 ), decision-making (Aslakson et al 2010 ; Monteiro et al 2016 ; Simmonds 1996 ; Svantesson et al 2003 ) and relationships (Almansour et al 2019 ; Amati and Hannawa 2014 ; Asch et al 1995 ; Baggs et al 2012 ; Brooks et al 2017b ; Chikhladze et al 2016 ; Cohen et al 2005 ; Gutierrez 2012 ; Hamric and Blackhall 2007 ; Hawryluck et al 2002 ; Henrich et al 2016 ; Hough et al 2005 ; Laurent et al 2017 ; Monteiro et al 2016 ; Simmonds 1996 ; Trankle 2014 ; Wåhlin et al 2010 ; Weng et al 2011 ; Workman et al 2003 ) of ICU physicians have been reported. In addition, how these physicians have come to view their professional responsibilities, and how they perceive the meeting of their professional duties and interactions, have evolved (Aslakson et al 2010 ; Brooks et al 2017a , 2017b ; Donnelly and Psirides 2015 ; Festic et al 2012 ; Hamric and Blackhall 2007 ; Jensen et al 2013 ; Laurent et al 2017 ; McAndrew and Leske 2015 ; Mehter et al 2018 ; Nordgren and Olsson 2004 ; Robertsen et al 2019 ; Svantesson et al 2003 ; Trankle 2014 ; Wåhlin et al 2010 ; Zambrano et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%